ماحولیاتی تغیرات اور مذہبی تنظیموں کی ذمہ داریاں؛ سیرت طیبہ ﷺ کا خصوصی مطالعہ: Environmental Changes and the Responsibilities of Religious Organizations; A foxed Study in the light of Seerah of the Holy Prophetﷺ - Dr. Muhammad Umar Farooq,; Dr. Hafiz Ruvaifa Khan, (Al-Amīr Research Journal for Islamic Studies, 2025)
Allah has set the example of Prophet Muhammad (peace be upon him) as a model for adhering to divine commandments, including guidance on worship and social life. It highlights the importance of a healthy environment for both physical and spiritual well-being. The Prophet taught the significance of cleanliness in rituals and promoted environmental protection, advising the sparing use of water and prohibiting harm to nature during Hajj. Today, environmental pollution poses significant challenges, leading thinkers to seek solutions and prompting legislative efforts for environmental protection globally. In Pakistan, measures and laws were established for this purpose, culminating in the formation of the Pakistan Environmental Protection Council. It calls for individuals and religious organizations to draw on the Prophet's example to address environmental issues, particularly climate change. Keywords: Divine commandments, Environment, Spiritual & Physical well-being, Cleanliness, Environmental protection